Corporate boards of large companies: More momentum needed for gender parity - Elke Holst; Anja Kirsch (DIW Economic Bulletin, 2016)
Germany's large corporations still have a long way to go before achieving balanced representation of men and women on their boards. At the end of 2015, the share of women on the executive boards of the top 200 companies in Germany was a good six percent, an increase of less than one percentage point over 2014. The share of women on the supervisory boards of these top 200 companies was almost 20 percent although growth there has slowed. The DAX 30 performed slightly better in terms of women's representation: the proportion of women on the executive boards of these companies was just under ten percent at the close of 2015 and the equivalent figure for supervisory boards was almost 27 percent. (In both cases, this represented an increase of more than two percentage points). Of the over 100 companies obliged to comply with a statutory 30-percent share of women for all new supervisory board appointments from January 2016, almost 28 percent had already met this quota by the end of 2015. Just under one-third of the companies had achieved a share of at least 20 percent but still less than 30 percent of female supervisory board members and were therefore well on their way to fulfilling the quota. Almost half of all DAX 30 companies met the quota. However, it is highly unlikely that the lion's share of the remaining companies will follow these trailblazers voluntarily in the near future since 22 percent of the top 200 and 24 percent of TecDAX companies, as well as over one-third of SDAX companies, currently either have no female supervisory board members at all or at most one in ten. Moreover, the share of women on executive boards is extremely low in all the companies analyzed in the present study. Germany's companies still have a long and difficult path ahead of them in order to achieve increased representation of women on their corporate boards. This makes it all the more imperative to adopt a coordinated approach to improve the career prospects of women by means of stringent framework conditions, also encompassing fiscal and family policy.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; board composition; board diversity; boards of directors; corporate boards; Europe; female directors; gender equality; gender quota; Germany; listed companies; management; private companies; public companies; supervisory boards; women CEOs; women's quota